2016
DOI: 10.3389/fpls.2016.00439
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming Alters the Production and Detoxification of Reactive Oxygen Intermediates in Rice Seedlings Grown under Sub-optimal Temperature and Nutrient Supply

Abstract: The production and detoxification of reactive oxygen intermediates (ROIs) play an important role in the plant response to nutrient and environmental stresses. The present study demonstrated the behavior of growth, ROIs-production and their detoxification in primed and non-primed rice seedlings under chilling stress (18°C) and nitrogen-(N), phosphorus-(P), or potassium-(K) deprivation. The results revealed that chilling stress as well as deprivation of any mineral nutrient severely hampered the seedling growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 51 publications
4
104
0
2
Order By: Relevance
“…Plants have developed a complex antioxidative defense system, consist of non-enzymatic and enzymatic components to overcome the excessive production of ROS [18,19,42], however, the balance between ROS generation and antioxidant enzyme activities is critical in all plant species under stress conditions [12,43]. Among various anti-oxidants, the SOD involves in the [11,19,36]. In present study, antioxidant enzymes i.e., SOD, POD, CAT, GSH-PX, GR and GST activities were triggered under the drought, chilling and chilling + drought stress conditions (Figure9,10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plants have developed a complex antioxidative defense system, consist of non-enzymatic and enzymatic components to overcome the excessive production of ROS [18,19,42], however, the balance between ROS generation and antioxidant enzyme activities is critical in all plant species under stress conditions [12,43]. Among various anti-oxidants, the SOD involves in the [11,19,36]. In present study, antioxidant enzymes i.e., SOD, POD, CAT, GSH-PX, GR and GST activities were triggered under the drought, chilling and chilling + drought stress conditions (Figure9,10).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, non-enzymatic antioxidants like GSH, vitamin C (Vc) and vitamin E (V E ) were also been found crucial for stress tolerance in crop plants [11,19]. For instance, the GSH can directly detoxify the O 2•−, •OH, H 2 O 2 and therefore, contributes in stress tolerance in plants [18,42,43,52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corrales et al (2008) reported that B is needed for plants to protect roots from oxidative damage under Al stress by improving defense system. The plants have evolved defense system consisting of both enzymatic as well as non-enzymatic components in order to better handle this elevated oxidative stress (Hussain et al 2016). In the cascade of the enzymatic system, SOD is the first enzyme that transforms damaging free radicals to H 2 O 2 and O 2 , (Noctor and Foyer 1998).…”
Section: Discussionmentioning
confidence: 99%